THE RELATIONSHIP BETWEEN THE USE OF BLENDED LEARNING MODEL AND IPS LEARNING OUTCOMES - ismiyati, lisa (Universitas Lambung Mangkurat, 2025)
The use of blended learning models can provide convenience and help students to carry out learning effectively and efficiently so that they can obtain maximum learning outcomes. The purpose of this studyto describe the relationship between the use of the blended learning model (X) consisting of sub-variables of face-to-face learning (X1), online learning (X2), and independent learning (X3) with the learning outcomes (Y) of junior high school students in Bandung City.This study uses a correlational study through a quantitative approach and distributes questionnaires with random sampling to 400 students of junior high schools in Bandung City. The results of the study explain that the subvariable of face-to-face learning has a coefficient value of 0.539 with a significance value of 0.000 <0.05, online learning is 0.657 with a significance value of 0.000 <0.05 and independent learning is 0.615 with a significance value of 0.000 <0.05 which means it has a significant relationship with learning outcomes. The results of the blended learning correlation test obtained a coefficient value of 0.764 with a significance value of 0.000 <0.05, so it can be concluded that Ha is accepted and Ho is rejected, which means there is a strong and significant positive relationship between the use of the blended learning model and the learning outcomes of social studies in junior high schools in Bandung City.